On some approaches to model reversible magnetization processes. (16th March 2018) - Chwastek, K; Baghel, A P S; Sai Ram, B; Borowik, B; Daniel, L; Kulkarni, S V
Abstract: This paper focuses on the problem of how reversible magnetization processes are taken into account in contemporary descriptions of hysteresis curves. For comparison, three versions of the phenomenological T ( x ) model based on hyperbolic tangent mapping are considered. Two of them are based on summing the output of the hysteresis operator with a linear or nonlinear mapping. The third description is inspired by the concept of the product Preisach model. Total susceptibility is modulated with a magnetization-dependent function. The models are verified using measurement data for grain-oriented electrical steel. The proposed third description represents minor loops most accurately.